2018
DOI: 10.1080/19375247.2018.1562600
|View full text |Cite
|
Sign up to set email alerts
|

Performance-based Design of Energy Pile Foundations

Abstract: Over the past twenty years, an increasing amount of research has been performed to understand the multiphysical behavior and to address the geotechnical and structural design of so-called energy piles, i.e., deep foundations that can serve any superstructure as both structural supports and geothermal heat exchangers. The coupled application of thermal and mechanical loads to energy piles, due to their multifunctional operation, represents a challenge. Currently, knowledge about the response of energy piles sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…The load transfer mechanism of the energy pile subjected to coupled thermal and mechanical effects had been studied by Bourne-Webb et al 30 and Rotta Loria et al 31 .…”
Section: Analytical Model For Representative Temperature Change In Pi...mentioning
confidence: 99%
“…The load transfer mechanism of the energy pile subjected to coupled thermal and mechanical effects had been studied by Bourne-Webb et al 30 and Rotta Loria et al 31 .…”
Section: Analytical Model For Representative Temperature Change In Pi...mentioning
confidence: 99%
“…Several researches have been conducted to investigate the role of thermal loading in the geotechnical design of energy piles. It was suggested that the effect of thermal loading must be considered in the analysis and design of energy piles 10 . Compared with the ultimate limit state, the performance degradation of the energy piles due to the piping need in the serviceability limit state was suggested to be more considered in the design (e.g., 6 ).…”
Section: Deterministic Design Model For Energy Pilesmentioning
confidence: 99%
“…Thus, besides satisfying the design requirements for traditional piles, the thermal loading should be properly considered in the design of energy piles. Several analysis methods have been developed to investigate the thermomechanical behavior of energy piles, such as the empirical method (e.g., 8 10 ), load-transfer method (e.g., 11 – 13 ), and Full numerical method (e.g., 14 16 ). However, it is still difficult to ascertain the pile performance in the geotechnical design of energy piles due to the uncertainties in soil parameters, applied load, design model, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Appropriate selection of design temperature variations, through due account of the non-uniformity of the temperature field within energy piles (Abdelaziz and Ozudogru 2016b), is necessary for verification purposes of these and other energy geostructures (Rotta Loria 2019;Rotta Loria et al 2020).…”
Section: Trends Of Average Temperature and Thermally Induced Vertical Stressmentioning
confidence: 99%